Implementasi Sistem E-Commerce dalam Meningkatkan Pemasaran UMKM di Kota Denpasar (Studi Kasus: Dinas Perindustrian dan Perdagangan Kota Denpasar) - Wulandari, Ni Luh Ayu; Supriliyani, Ni Wayan; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2019)
zABSTRACT InqtheqPresidentialqRegulation Number 74 of 2017 about E-Commerce Roadmap stated that inzorderztozincreasezthe public service performancezofzThe Regional Government of Denpasar, the Government will provide E-Commerce system. The system would help SMEs in doing online transactions. This research discusses deeper about thezeffectzofzE-Commerce program for increasing the marketing of SMEs in Denpasar which would be the place for SMEs and craftsmen to expand their business. Many SMEs still unable to market their products. This researchzaims to discuss about thezimplementationzofzE-Commerce system in increasing the marketing of SMEs in Denpasar. Thezunitzofzanalysiszinzthiszresearch is The Department of Industry and Trade of Denpasar and the research will use descriptive qualitative method. Keywords: Implementation, E-Commerce system, SME